Requirement analysis of development of integrated islamic values laboratory worksheets using flip PDF professional applications in general biology courses - Meliyani Meliyani; H. Mukhlis Rohmadi; Ridha Nirmalasari (Jurnal Pijar Mipa, 2022)
A needs analysis has been carried out for the development of a laboratory worksheet based on Islamic values in general biology courses. Needs analysis was carried out through interviews with general biology lecturers, laboratory work assistants and students. The activity was also followed by a field study. The data analysis technique is qualitative descriptive analysis. The results of the interviews showed that 1. the laboratory work module used was unattractive and impractical so that it made it difficult for students to understand work procedures, 2) the laboratory work module used had not been integrated with Islamic values so that it was not in accordance with the learning plan made by the lecturer. The results of the needs analysis showed that the lecturers and laboratory work assistants strongly agreed to use general biology laboratory work guidelines integrated with Islamic values using the Flip PDF Professional application. Furthermore, 95.5% of students stated the need for the development of laboratory work integrated with Islamic values. 54.5% of students stated that general biology laboratory work is difficult to understand. 72.2% of students agree that the developed guide is in the form of an e-book and 95.5% of students want to develop a practical and interesting general biology laboratory work guide.